PENGARUH LINGKUNGAN KERJA DAN BEBAN KERJA TERHADAP MOTIVASI KERJA : STUDI KASUS DI BALAI BESAR PENGUJIAN PENERAPAN PRODUK KELAUTAN DAN PERIKANAN SELAMA PANDEMI COVID-19 - Fitri Arisanti (2021)
The purpose of this research is to analyze and test the effect partially and simultaneously between work environment and workload on employee work motivation. This research used a quantitative approach with several methods including interview, observation and questionere and with the help of PLS 3.0 program to analyze and calculate. The sample of research 93 employees at the Center for Testing the Application of Marine and Fishery Products. There are several conclusions that can be found from the results of this study and that is: (1) Work environment had a positive and significant effect on the work motivation of BBP3KP employees (2) Workload had a significant and positive effect on employees work motivation (3) Between work environment and workload there is simultaneous significant effect on work motivation of BBP3KP employees